Halubilo a mixed community housing development for socio-economic inclusion in Philippine urban communities - Carballo, Alysza Mé M.
In the face of the current global pandemic, increased attention has been given to numerous social issues caused by Social Distancing and Community Quarantines. Evidently, these have brought to light deeply rooted problems regarding the lack of Social Inclusion in Filipino communities. As an architectural solution, Social Inclusion encompasses the improvement of interaction, ability, opportunity and dignity of the community on the basis of their identity. Applying this to housing provides an opportunity to target smaller units of the society, and to create a more tight-knitted community. In the Philippines, there is yet to be a truly inclusive housing development that represents people from various backgrounds and socio-economic levels. On the other hand, western countries have been implementing an architectural program that requires developers of housing estates to provide public housing integrated within open market units. This program, called Mixed Income Housing has showed promise especially in uplifting the lives of lower income residents. Mixed Income Housing, when done right, creates a tight knit and lively community that mutually benefits all residents in the area. Moreover, it can act as a vehicle to create social mix, social interactions, and ultimately social inclusion amongst residents of different socio-economic levels. With the current housing situation in the country, a new typology of housing is needed in order to create better and longer-lasting Filipino communities. Using the idea of Mixed Income Housing a socially mixed housing development in Angeles is proposed. The level of income mix was determined from similarities in the jobs, routines, wants, and needs of the residents. The similarities were also used to determine the different spaces needed inside the housing development. The amenities provided and the approach used in designing focused on improving the individual and the community holistically.